Ectoparasites and endoparasites on baree (Lingula anatina, Lamarck 1801) at Ujung Pancu Beach, Aceh Besar - Octavina, Chitra; Farahisah, Harum; Pratiwi, Cintya Indria; Damora, Adrian (Depik, 2025)
Lingula anatina or also known as baree is an animal that has legs and no spine. Baree is one of the few marine avertebrates that has the most complete fossil record, this species can play a role in ecological monitoring and maintaining the health of marine ecosystems. This study aims to identify and analyze the types of ectoparasites and endoparasites as well as measure the prevalence and intensity of infection in Lingula anatina (baree) at Ujung Pancu Beach, Aceh Besar. The results showed the presence of ectoparasites Pedicellina cernua (Entoprocta) and Unitubilotestis sp. (Platyhelminthes), as well as endoparasites Perkinsus spp. (Perkinsozoa) and Hysterothylacium aduncum (Nematoda). The prevalence of ectoparasite infection ranged from 0.08%, with an intensity of 1 individual per sample, while the prevalence of endoparasites ranged from 0.03%-0.22% with an intensity of 1.45-2.81 individuals per sample. These findings add insight into the parasites infecting Lingula anatina and contribute to ecological monitoring and marine ecosystem health.Keywords:L. anatinaFilter feederNematodaPlatyhelminthes